2009
DOI: 10.1007/s10764-009-9341-6
|View full text |Cite
|
Sign up to set email alerts
|

The Social System of Lariang Tarsiers (Tarsius lariang) as Revealed by Genetic Analyses

Abstract: Previous sociobiological studies of tarsiers were invariably based on field observations. Sulawesi tarsiers are known for monogamous or facultative polygynous social mating systems, but, to date, no data exist to describe the genetic mating system. We here bring together behavioral studies and molecular tools for the first time to elucidate mating behavior and kinship within a tarsier population. We investigated the social system of the recently described Tarsius lariang, which researchers have never studied b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Blomqvist et al, 2002;Stapleton et al, 2007;Suter et al, 2007;Varian-Ramos & Webster, 2012), but evidence in monogamous mammals is limited. Combined with evidence from studies of other monogamous species including Alpine marmots Marmota marmota and Lariang tarsiers Tarsus lariang (Cohas et al, 2008;Driller et al, 2009), our results suggest that, like birds, female mammals may use extra-pair mating when paired with a related male.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Blomqvist et al, 2002;Stapleton et al, 2007;Suter et al, 2007;Varian-Ramos & Webster, 2012), but evidence in monogamous mammals is limited. Combined with evidence from studies of other monogamous species including Alpine marmots Marmota marmota and Lariang tarsiers Tarsus lariang (Cohas et al, 2008;Driller et al, 2009), our results suggest that, like birds, female mammals may use extra-pair mating when paired with a related male.…”
Section: Discussionsupporting
confidence: 74%
“…In birds, rates of EPC and, to a smaller extent, divorce have often been shown to be related to genetic relatedness between pair mates (Kempenaers et al, 1998;Blomqvist et al, 2002;Freeman-Gallant et al, 2003;Van de Casteele et al, 2003;Tarvin et al, 2005). In mammals, although some studies have shown that nonmonogamous females preferentially choose unrelated partners (Hoffman et al, 2007), very few studies have investigated the relationship between within-pair relatedness and rates of EPC in socially monogamous species (Cohas et al, 2008;Driller et al, 2009). To the best of our knowledge, studies are limited to Alpine marmots Marmota marmota and Lariang tarsiers Tarsius lariang, where extra-pair young (EPY) are more frequent when pairs exhibit close relationships (Cohas et al, 2008;Driller et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Among pair-living nocturnal primates fork-marked lemurs ( Phaner pallescens : Schülke and Kappeler 2003), dwarf lemurs ( Cheirogaleus medius : Fietz 1999), dwarf galagos ( Galagoides zanzibaricus : Nash and Harcourt 1986), tarsiers ( Tarsius spp. : Driller et al 2009; Gursky-Doyen 2010), woolly lemurs ( Avahi spp. : Harcourt 1991), and owl monkeys ( Aotus spp.…”
Section: Discussionmentioning
confidence: 99%
“…The usually higher number of adult females than adult males in a group could mean that female offspring leave their natal group at a later stage than adolescent males. In a recent population genetic study on T. lariang, a species occurring parapatrically to T. dentatus, very similar group compositions were revealed (Driller et al 2009). …”
Section: Group Compositionmentioning
confidence: 90%